2023
DOI: 10.3390/rs15225349
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Multiple Satellite, Reanalysis, and Merged Precipitation Products for Hydrological Modeling in the Data-Scarce Tributaries of the Pearl River Basin, China

Zhen Gao,
Guoqiang Tang,
Wenlong Jing
et al.

Abstract: Satellite and reanalysis precipitation estimates of high quality are widely used for hydrological modeling, especially in ungauged or data-scarce regions. To improve flood simulations by merging different precipitation inputs or directly merging streamflow outputs, this study comprehensively evaluates the accuracy and hydrological utility of nine corrected and uncorrected precipitation products (TMPA-3B42V7, TMPA-3B42RT, IMERG-cal, IMERG-uncal, ERA5, ERA-Interim, GSMaP, GSMaP-RNL, and PERSIANN-CCS) from 2006 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Concurrently, JRA55, NCEP-NCAR and NCEP-DOE were adjusted to a 0.5 • resolution through the application of the inverse distance weighting interpolation method. These methods have been extensively utilized in prior studies and have shown a high level of effectiveness [11,15,53,54]. The daily rain gauge observations used in this paper were collected from the Global Summary of the Day database (https://data.noaa.gov, accessed on 1 April 2024) and the China Meteorological Administration website (http://data.cma.cn/, accessed on 1 April 2024).…”
Section: Global Precipitation Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrently, JRA55, NCEP-NCAR and NCEP-DOE were adjusted to a 0.5 • resolution through the application of the inverse distance weighting interpolation method. These methods have been extensively utilized in prior studies and have shown a high level of effectiveness [11,15,53,54]. The daily rain gauge observations used in this paper were collected from the Global Summary of the Day database (https://data.noaa.gov, accessed on 1 April 2024) and the China Meteorological Administration website (http://data.cma.cn/, accessed on 1 April 2024).…”
Section: Global Precipitation Datasetsmentioning
confidence: 99%
“…These datasets exhibit substantial variability with respect to data sources, spatial coverage and resolution, temporal span and resolution, among other factors [8][9][10]. According to data sources, these precipitation datasets fall into four categories: (1) gauge-based, (2) satellite-based, (3) reanalysis and (4) merged [8,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Regions with large bodies of water, such as Sobradinho, have a considerable capacity to retain solar radiation, which makes these areas more suitable for data capture due to the occurrence of optical processes relevant to remote sensing [82]. This renders such data highly reliable for estimations regarding water bodies, such as hydrographic basins [83,84]. Throughout the period represented by the CDD (Figure 3a), precipitation occurred in a well-distributed manner.…”
Section: Mean Precipitation Intensity Indexmentioning
confidence: 99%